Alterations of lipid metabolism in Wilson disease - Seeßle, Jessica; Gohdes, Marion Annina; Gotthardt, Daniel; Pfeiffenberger, Jan; Eckert, Nicola; Stremmel, Wolfgang; Reuner, Ulrike; Weiss, Karl Heinz (Lipids in health and disease, 2011)
Wilson disease (WD) is an inherited disorder of human copper metabolism, characterised by accumulation of copper predominantly in the liver and brain, leading to severe hepatic and neurological disease. Interesting findings in animal models of WD (Atp7b-/- and LEC rats) showed altered lipid metabolism with a decrease in the amount of triglycerides and cholesterol in the serum. However, serum lipid profile has not been investigated in large human WD patient cohorts to date.